Manual de la Ley de Propiedad y Cercado de Florida: Tabla del Contenido - Michael T. Olexa; Joshua A. Cossey (EDIS, 2007)
Spanish version of the "Florida Fence and Property Law" handbook by Michael T. Olexa and Joshua A. Cossey. Published July 2007.